ANALYSIS OF CUSTOMER EXPERIENCE AND CUSTOMER SATISFACTION OF GOJEK APPLICATION BASED INFORMATION TECHNOLOGY SERVICES IN MANADO - Kalangi, Kevin .; Pangemanan, Sifrid S.; Pandowo, Merinda . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Technology is affecting the life of every individual both qualitatively and quantitatively in the present age. The quick expansion of information technology has imbibed into the lives of millions of people and introduced major changes in the worldwide economic and business atmosphere. This research aims to analyze the customer experience and customer satisfaction of Go-Jek application in Manado. Technology is utilized by one of the online transportation companies in Indonesia, namely PT.Go-Jek Indonesia.With the existence of PT.Go-Jek Indonesia, create a new digital era in the Indonesia market, especially in technology services. People now have so many services that can be order through the Go-Jek application-based information technology in a smartphone. PT.Go-Jek Indonesia provide something thats really needed in the society.In the Go-Jek application there is available a variety of service to offer for consumers and several feature that’s already available in Manado that is to order food (Go-Food), transportation (Go-Ride for motorcycle and Go-Car for car), send goods or things (Go-Send), cashless transaction system (Go-Pay), buy in a particular shop (Go-Mart). The type of this research is qualitative research. The method used in this research is snowball sampling that get 12 respondents who fulfill the requirement to be interviewed.Keywords: information technology, customer experience, customer satisfaction, go-jek.